Association of Serum Interleukin-8 and Serum Amyloid A With Anxiety Symptoms in Patients With Cerebral Small Vessel Disease - Shan, Li-Li; Wang, Yi-Lin; Qiao, Tian-Ci; Bian, Yue-Feng; Huo, Ya-Jing; Guo, Cen; Liu, Qian-Yun; Yang, Zi-Dong; Li, Ze-Zhi; Liu, Ming-Yuan; Han, Yan (Frontiers in Neurology, 2022)
Objective Cerebral small vessel disease (CSVD) is a clinical syndrome caused by pathological changes in small vessels. Anxiety is a common symptom of CSVD. Previous studies have reported the association between inflammatory factors and anxiety in other diseases, but this association in patients with CSVD remains uncovered. Our study aimed to investigate whether serum inflammatory factors correlated with anxiety in patients with CSVD. Methods A total of 245 CSVD patients confirmed using brain magnetic resonance imaging (MRI) were recruited from December 2019 to December 2021. Hamilton Anxiety Rating Scale (HAMA) was used to assess the anxiety symptoms of CSVD patients. Patients with HAMA scores ≥7 were considered to have anxiety symptoms. The serum levels of interleukin-1β (IL-1β), IL-2R, IL-6, IL-8, IL-10, tumor necrosis factor-α (TNF-α), serum amyloid A (SAA), C-reactive protein (CRP), high-sensitivity C-reactive protein (hs-CRP) and erythrocyte sedimentation rate (ESR) were detected. We compared levels of inflammatory factors between the anxiety and non-anxiety groups. Logistic regression analyses examined the correlation between inflammatory factors and anxiety symptoms. We further performed a gender subgroup analysis to investigate whether this association differed by gender. Results In the fully adjusted multivariate logistic regression analysis model, we found that lower levels of IL-8 were linked to a higher risk of anxiety symptoms. Moreover, higher levels of SAA were linked to a lower risk of anxiety symptoms. Our study identified sex-specific effects, and the correlation between IL-8 and anxiety symptoms remained significant among males, while the correlation between SAA and anxiety symptoms remained significant among females. Conclusions In this study, we found a suggestive association between IL-8, SAA, and anxiety symptoms in CSVD participants. Furthermore, IL-8 and SAA may have a sex-specific relationship with anxiety symptoms.